In Situ X-Ray Tomography Imaging of Soil Water and Cyanobacteria From Biological Soil Crusts Undergoing Desiccation - Couradeau, Estelle; Felde, Vincent J. M. N. L.; Parkinson, Dilworth; Uteau, Daniel; Rochet, Alexis; Cuellar, Charlene; Winegar, Geoffrey; Peth, Stephan; Northen, Trent R.; Garcia-Pichel, Ferran (Frontiers in Environmental Science, 2018)
Biological soil crusts (biocrusts) are millimeter-sized microbial communities developing on the topsoils of arid lands that cover some 12% of Earth’s continental area. Biocrusts consist of an assemblage of mineral soil particles consolidated into a crust by microbial organic polymeric substances that are mainly produced by the filamentous bundle-forming cyanobacteria, among which Microcoleus vaginatus is perhaps the most widespread. This cyanobacterium is the primary producer for, and main architect of biocrusts in many arid soils, sustaining the development of a diverse microbial community. Biocrusts are only active when wet, and spend most of their time in a state of desiccated quiescence, from which they can quickly recover upon wetting. Despite their ecological importance for arid ecosystems, little is known about the mechanisms that allow biocrust organisms to endure long periods of dryness while remaining viable for rapid resuscitation upon wetting. We had previously observed the persistence of significant rates of light-dependent carbon fixation in apparently dry biocrusts dominated by M. vaginatus, indicating that it may be able to remain hydrated against a background soil of very low water potential. One potential explanation for this may be that the abundant exopolysaccharide sheaths of M. vaginatus can preferentially retain moisture thus slowing the water equilibration with the surrounding soil allowing for extended activity periods. In order to test this hypothesis we aimed to develop methodologies to visualize and quantify the water dynamics within an undisturbed biocrust undergoing desiccation. We used synchrotron based X-ray microtomography and were able to resolve the distribution of air, liquid water, mineral particles and cyanobacterial bundles at the microscale. We could demonstrate the formation of steep, decreasing gradients of water content from the cyanobacterial bundle surface outward, while the bundle volume remained stable, as the local bulk water content decreased linearly, hence demonstrating a preferential retention of water in the microbes. Our data also suggest a transfer of hydration water from the EPS sheath material into the cyanobacterial filament as desiccation progresses. This work demonstrates the value of X-ray tomography as a tool to study microbe-scale water redistribution in biocrusts.